Amide–imine conjugate involving gallic acid and naphthalene for nano-molar detection, enrichment and cancer cell imaging of La3+: studies on the catalytic activity of the La3+ complex. (29th July 2020) - Shaikh, Ahad; Ghosh, Milan; Mukherjee, Pallabi; Ghosh, Avijit; Molla, Rostam Ali; Ta, Sabyasachi; Das, Debasis
Abstract : A single crystal X-ray structurally characterized amide–imine conjugate (GAN ) derived from gallic acid and naphthalene selectively recognizes La 3+ ion via TURN ON fluorescence through ESIPT and CHEF mechanisms. Abstract : A single crystal X-ray structurally characterized amide–imine conjugate (GAN ) derived from gallic acid and naphthalene selectively recognizes La 3+ ions via TURN ON fluorescence through ESIPT and CHEF mechanisms. GAN can detect as low as 23.93 × 10 −9 M La 3+ ions and image intracellular La 3+ ions in live HeLa and SiHa cells under a fluorescence microscope in a time- and concentration dependent manner. The corresponding [La(iii )–GAN ] complex is established as an efficient catalyst for the synthesis of benzimidazole derivatives from o -phenylenediamine and substituted benzaldehydes. Moreover, GAN is very useful for enrichment of La 3+ in ethyl acetate medium.